A cluster randomized theory‐guided oral hygiene trial in adolescents—A latent growth model. Issue 2 (17th May 2017) - Aleksejūnienė, J; Brukienė, V
Abstract: Objectives: (i) To test whether theory‐guided interventions are more effective than conventional dental instruction (CDI) for changing oral hygiene in adolescents and (ii) to examine whether such interventions equally benefit both genders and different socio‐economic (SES) groups. Methods: A total of 244 adolescents were recruited from three schools, and cluster randomization allocated adolescents to one of the three types of interventions: two were theory‐based interventions (Precaution Adoption Process Model or Authoritative Parenting Model) and CDI served as an active control. Oral hygiene levels % (OH) were assessed at baseline, after 3 months and after 12 months. Results: A complete data set was available for 166 adolescents (the total follow‐up rate: 69%). There were no significant differences in baseline OH between those who participated throughout the study and those who dropped out. Bivariate and multivariate analyses showed that theory‐guided interventions produced significant improvements in oral hygiene and that there were no significant gender or socio‐economic differences. Conclusions: Theory‐guided interventions produced more positive changes in OH than CDI, and these changes did not differ between gender and SES groups.